Pengaruh Perputaran Modal Kerja dan Perputaran piutang Pada Tingkat Profitabilitas PT Uniliver Indonesia Tbk pada tahun 2016-2020 - Windiana Hastuti; Wagini Wagini; Abdul Rahman (UNIVED Press, 2022)
This study aims to analyze the effect of working capital turnover and receivables turnover on profitability (ROA). This analysis uses the independent variables of working capital turnover, receivables turnover. while the dependent variable is profitability, namely ROA.The data used are secondary data derived from the annual financial statements of PT. Unilever Indonesia tbk which is listed on the Indonesia Stock Exchange for the period 2016 to 2020. The data testing method uses classical assumption test, multiple linear regression, coefficient of determination (R2), with hypothesis testing t test and f test. The results of the study using multiple linear regression test with t-test Working Capital Turnover of 8.430 > Ttable (4,302) which means that Working Capital Turnover has an influence on profitability. The Accounts Receivable Turnover variable has a value of Tcount (1.713) which is smaller than Ttable (4.302) where Working Capital has an influence on profitability at PT. Unilever Indonesia Tbk. Meanwhile, hypothesis testing using the Simultaneous F Test shows that the calculated F value is greater than the F value. t table. F count is 34,385 > Ftable 9.552. Significant values ​​on all variables show that they are smaller than 0.05, which means that each variable has a simultaneous effect on the profitability of the company.